PERAN MUDA DALAM MEMAJUKAN PENDIDIKAN INDONESIA - Nabila Aulya Marsya; Fatimah Putri Ayu; Aulia Dema Andini; Rian Dinata; Amnah, Amnah (Cahaya Ilmu Bangsa Institute, 2024)
Significant changes in education require the involvement of the younger generation as agents of change. This article discusses the important role of the younger generation in improving the quality of education in Indonesia through a descriptive qualitative approach. Data was obtained from the video interview “Bincang Ganesha” which highlights the importance of small actions with big impacts for the advancement of education. The research shows that relevant innovations, character-based education, and utilization of technology can help the younger generation. To solve issues such as unequal access and lack of awareness of the importance of 21st century skills, teachers and students must work together to create an inclusive and adaptive learning atmosphere. Therefore, the younger generation is crucial in improving education and making it fit the needs of society.